Delamination-fretting wear failure evaluation at HAp-Ti-6Al-4V interface of artificial hip implant - Muniandy, Nagentrau (2021)
Osteoarthritis due to rapid aging population in Malaysia and developed countries leads to an extensive application of titanium artificial hip implants. However, titanium alloys (Ti-6Al-4V) cannot directly adhere with human bone due to bio-compatibility issue. Thus, Hydroxyapatite (HAp:Ca10(PO4)(OH)2) coating which consists of main composition of human bone is plasma sprayed on titanium implants to maintain fixations during bone in-growth process. HAp coatings are susceptible to fail due to brittle fractures (coating through thickness crack) to initiate delamination which promotes fretting wear behaviour. Fretting wear particles are concerned for activating inflammations at surrounding organs, which lead to loosening of implants or subsequent failures. Present research aims to develop a finite element model to examine delamination-fretting wear behaviours that can suitably mimic actual loading conditions at HAp-Ti-6Al-4V interface of hip implant femoral stem component to formulate maximum wear depth predictive equation as a novel and fast failure prediction tool. Three simple finite element contact configuration models subjected to different mechanical and tribological properties consist of contact pad (bone), HAp coating and Ti-6Al-4V substrate are developed using contact modelling, cohesive zone modelling (CZM) and adaptive wear modelling (UMESHMOTION) approaches to be examined under static simulation. The developed finite element models are validated and verified with modified Hertzian theoretical solution and reported literatures. The findings revealed that significant delamination-fretting wear is recorded at contact edge (leading edge) as a result of substantial contact pressure and contact slip driven by stress singularity effect. Tensile-compressive condition (R = -1 ) experiences most significant delamination-fretting wear behaviour (8 times higher) compared to stress ratio R = 0.1 and R = 10. Finally, maximum delamination-fretting wear depth predictive equations are successfully formulated with significant goodness of fit and reliability as a fast failure prediction tool.